A Life Course Study of Genetic and Environmental Influences on Work Incapacity. (26th February 2020) - Seglem, Karoline B.; Torvik, Fartein A.; Røysamb, Espen; Gjerde, Line C.; Magnus, Per; Reichborn-Kjennerud, Ted; Svedberg, Pia; Ørstavik, Ragnhild
Abstract: Work incapacity is a major public health challenge and an economic burden to both society and individuals. Understanding the underlying causes is becoming ever more relevant as many countries face an aging workforce. We examined stability and change in genetic and environmental factors influencing work incapacity from age 18 until retirement, and sex differences in these effects. The large population-based sample comprised information from 28, 759 twins followed for up to 23 years combined with high-quality national registry data. We measured work incapacity as the total proportion of potential workdays lost due to sickness absence, rehabilitation and disability benefits. Structural equation modeling with twin data indicated moderate genetic influences on work incapacity throughout life in both men and women, with a high degree of genetic stability from young to old adulthood. Environmental influences were mainly age-specific. Our results indicate that largely the same genetic factors influence individual differences in work incapacity throughout young, middle and older adulthood, despite major differences in degree of work incapacity and probable underlying medical causes.